Loss of normal cyclical beta 2 adrenoceptor regulation and increased premenstrual responsiveness to adenosine monophosphate in stable female asthmatic patients - Tan, K. S. (BMJ Group, 1997)
BACKGROUND: A study was undertaken to investigate the influence of the menstrual cycle on airway responsiveness and beta 2 adrenoceptor function in female asthmatic patients. It has previously been shown that normal women exhibit cyclical changes in beta 2 adrenoceptor function with an increase in beta 2 adrenoceptor density in the luteal phase during the premenstrual period. METHODS: Fifteen women with stable, well controlled asthma (mean forced expiratory volume in one second (FEV1) 2.971 (93.8% predicted)) were evaluated. Measurements were made at the follicular phase (days 1-6) and the luteal phase (days 21-24) of the menstrual cycle. Airway responsiveness was assessed using adenosine 5'-monophosphate (AMP) and expressed as PC20 AMP. Beta 2 adrenoceptor function was evaluated by measuring lymphocyte beta 2 adrenoceptor parameters and constructing dose-response curves to salbutamol (100-1600 micrograms). The levels of female sex hormones were also measured at both phases of the cycle. RESULTS: There were significant increases in serum levels of both oestradiol (2.2-fold, p < 0.001) and progesterone (7.2-fold, p < 0.05) between the follicular and luteal phases. Geometric mean PC20 AMP was 19.0 mg/ml and 7.6 mg/ml during the follicular and luteal phases, respectively (p < 0.05), a 2.51-fold difference (95% CI 1.19 to 5.30) amounting to 1.33 doubling doses of AMP. There was no change in lymphocyte beta 2 adrenoceptor parameters or in airway beta 2 adrenoceptor responses to salbutamol between the two phases. CONCLUSIONS: Despite an appropriate rise in female sex hormones during the luteal period, beta 2 adrenoceptor regulation in female asthmatic subjects shows a loss of the normal cyclical pattern. In addition, there were cyclical changes in airway responsiveness to AMP which was highest during the premenstrual period. Thus, drugs such as theophylline which block adenosine receptors warrant investigation in premenstrual asthma.